Comparison of Treatment-Related Toxicity With Hypofractionated or Conventionally Fractionated Radiation Therapy for Prostate Cancer: A National Population-Based Study. Issue 8 (August 2020) - Sujenthiran, A.; Parry, M.; Nossiter, J.; Berry, B.; Cathcart, P.J.; Clarke, N.W.; Payne, H.; van der Meulen, J.; Aggarwal, A.
Abstract: Aims: Randomised controlled trials have shown comparable early oncological outcomes after hypofractionated and conventionally fractionated radiotherapy in the radical treatment of prostate cancer (PCa). The effect of hypofractionation on treatment-related gastrointestinal and genitourinary toxicity remains uncertain, especially in older men and those with locally advanced PCa. Materials and methods: A population-based study of all patients treated with radical conventionally fractionated radiotherapy ( n = 9106) and hypofractionated radiotherapy ( n = 3027) in all radiotherapy centres in the English National Health Service between 2014 and 2016 was carried out. We identified severe gastrointestinal and genitourinary toxicity using a validated coding framework and compared conventionally fractionated and hypofractionated radiotherapy using a competing-risks proportional hazards regression analysis. Results: The median age in our cohort was 72 years old and most patients had locally advanced disease (65%). There was no difference in gastrointestinal toxicity (conventionally fractionated radiotherapy: 5.0 events/100 person-years; hypofractionated radiotherapy: 5.2 events/100 person-years; adjusted subdistribution hazard ratio: 1.00, 95% confidence interval: 0.89–1.13; P = 0.95) or genitourinary toxicity (conventionally fractionated radiotherapy: 2.3 events/100 person-years; hypofractionated radiotherapy: 2.3 events/100 person-years; adjusted subdistribution hazard ratio: 0.92, 95% confidence interval: 0.77–1.10; P = 0.35) between patients who received conventionally fractionated radiotherapy and those who received hypofractionated radiotherapy. Conclusions: This national cohort study has shown that the use of hypofractionated radiotherapy in the radical treatment of PCa does not increase rates of severe gastrointestinal or genitourinary toxicity. Our findings also support the use of hypofractionated radiotherapy in older men and those with locally advanced PCa. Highlights: No difference in severe gastrointestinal and genitourinary toxicity between radical conventionally fractionated and hypofractionated radiotherapy for PCa. Results consistent in elderly men and those with locally advanced disease (under-represented in current RCTs). Our results from a large unselected 'real-world' population further support the use of radical hypofractionated in PCa.